Analysis of the application of the deep learning approach in mathematics learning for class x students of state senior high school 6 kediri city - Khusnul Arifah; Darsono Darsono; Dian Devita Yohanie (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
This study aims to describe the application of the Deep Learning approach in mathematics learning and examine its impact on student engagement and understanding of the Three-Variable Linear Equation System (SPLTV) material. The study used a qualitative approach with a descriptive design and was conducted at SMA Negeri 6 Kediri City. The research subjects consisted of one mathematics teacher and 36 students of grades X-10 who were selected purposively. Data collection was carried out through observation, semi-structured interviews, and documentation, with triangulation techniques to ensure data validity. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the application of the Deep Learning approach through simulation-based contextual learning provided a positive indication of student engagement and understanding. Students appeared more active in discussions, dared to express their opinions, and were able to relate mathematical concepts to real situations. Contextually designed learning also created a meaningful and enjoyable learning atmosphere. However, its implementation still faces obstacles, such as limited learning time and differences in student characteristics. These findings indicate that the Deep Learning approach has the potential to be an alternative mathematics learning strategy that can support the formation of a more meaningful and contextual learning experience.